Incidence of ?-lactamase producing Escherichia coli amongst clinical isolates in Dhaka, Bangladesh - Bhowmik, Anindita; Ahsan, Sunjukta; Akhtar, Marufa Zerin; Kabir, Md Shahidul (Stamford Journal of Microbiology, 2016)
Escherichia coli is one of the most important clinical pathogens that demonstrate antibiotic resistance through their ? -lactamase activity. The present study reflected on the presence of ?-lactam antibiotic resistance in clinical samples. Antibiotic resistance patterns of 20 clinical isolates of Escherichia coli against ? -lactam antibiotics were investigated. These isolates were collected from a hospital in Dhaka city and MIC values were determined against Imipenem, Cefotaxime and Ceftriaxone. In case of Ceftriaxone the highest MIC was >4096 ?g/mL for 50% isolates with a minimum MIC of 1 ?g/ml for 10% isolates. In case of Cefotaxime, MIC values ranged between 1 ?g/ml and >4096 ?g/ml for 20% and 10% isolates, respectively. In contrast, 80% of the isolates had an MIC of Imipenem at 1 ?g/mL with only 5% isolate having MIC of 8 ?g/mL. Eight out of 20 (40%) isolates were ESBL producers, 14 (70%) were ? -lactamase producers. Two isolates exhibited ESBL activity against Cefotaxime and Ceftriaxone, 3 against only Cefotaxime and 3 against only Ceftriaxone. Ceftriaxone resistance in 10 randomly picked isolates was found to be stable for 21days in stability assay. Considering the findings of the present study, it appears that Imipenem still remains the drug of choice for E. coli infections; alternatively, combination therapy may be prescribed. In vitro stability of Ceftriaxone resistance raises concern from a public health point of view as this may aid antibiotic resistance transfer to other bacteria in the environment. Stamford Journal of Microbiology, Vol.5(1) 2015: 18-21